Interviewing vulnerable suspects : safeguarding the process - Tudor-Owen, Jane (New York, NY : Routledge, 2023)
"This book is an in-depth, evidence-based guide to interviewing suspects with specific vulnerabilities. It provides an overview of current research, practices, and legal considerations for interviewing vulnerable suspects, incorporating guidelines regarding the identification of vulnerabilities, engaging with third parties in the interview, and training and supervision. It then goes on to cover specific vulnerabilities typically encountered in suspect populations, providing clear summaries of current research, case studies, and practical guidance for conducting interviews with these populations to facilitate best practice in interviewing. Expertise is drawn from both law enforcement practice and academic research to ensure an evidence-based approach that is relevant for contemporary practice. Interviewing Vulnerable Suspects offers the international policing audience a practical guide to interviewing vulnerable suspects for both uniform police and detectives. It is relevant for statutory bodies involved in investigations of misconduct; legal practitioners and forensic psychologists; practitioners in counselling, social work, and psychology; and students in policing, criminology and forensic psychology programs"--
OCLC-licensed vendor bibliographic record.
Keywords: Interviewing in law enforcement; Police questioning; Suspects (Criminal investigation); PSYCHOLOGY / Forensic Psychology; SOCIAL SCIENCE / Criminology